Non-integer IMC based PID Design for Load Frequency Control of Power System Through Reduced Model Order - Idamakanti Kasireddy; Abdul Wahid Nasir; Arun Kumar Singh (Institute of Advanced Engineering and Science, 2018)
This paper deals with non-integer internal model control (FIMC) based proportional-integral-derivative(PID) design for load frequency control (LFC) of single area non-reheated thermal power system under parameter divergence and random load disturbance. Firstly, a fractional second order plus dead time(SOPDT) reduced system model is obtained using genetic algorithm through step error minimization. Secondly, a FIMC based PID controller is designed for single area power system based on reduced system model. Proposed controller is equipped with single area non-reheated thermal power system. The resulting controller is tested using MATLAB/SIMULINK under various conditions. The simulation results show that the controller can accommodate system parameter uncertainty and load disturbance. Further, simulation shows that it maintains robust performance as well as minimizes the effect of load fluctuations on frequency deviation. Finally, the proposed method applied to two area power system to show the effectiveness.